Efficacy of electroacupuncture for the treatment of constipation in Parkinson's disease: study protocol for a multicentre randomised controlled trial. Issue 11 (27th November 2019) - Li, Kunshan; Wang, Zhaoqin; Chen, Yiyi; Shen, Lirong; Li, Zhongqiu; Wu, Yiwen; Yuan, Canxing; Huang, Yan; Wu, Luyi; Bao, Chunhui; Zhang, Wei; Xu, Shifen; et al.
Abstract : Introduction: Constipation is one of the most common non-motor symptoms in Parkinson's disease (PD). Acupuncture can have a positive on chronic functional constipation and PD, but its efficacy for the treatment of constipation in PD has not yet been confirmed by high-quality clinical trials. Therefore, this study aims to evaluate the efficacy and safety of electroacupuncture (EA) in the treatment of constipation in PD. Methods and analysis: This study is a multicentre randomised controlled trial. A total of 124 qualified patients with PD and constipation will be randomly divided into the intervention group (62 participants will receive 12 weeks of EA +usual care) or the waitlist control group (62 participants will receive 12 weeks of usual care). EA will be performed three times per week from weeks 1–8, two times per week during weeks 9 and 10, and once a week during weeks 11 and 12. The primary outcome is the change in mean weekly spontaneous bowel movements from baseline to weeks 8 and 9. The secondary outcomes are the changes from baseline in mean weekly bowel movements, mean weekly stool consistency, and mean weekly straining. Other secondary outcomes include the weekly doses of defecation drugs, Visual Analogue Scale for subjective improvements in stool symptoms, Unified Parkinson's Disease Rating Scale, and the time and number of steps required to walk 20 m. Outcomes will be assessed at baseline, week 4, 8, 12 (intervention period); as well as at week 16, 24 (follow-up period). Ethics and dissemination: Ethical approval has been obtained from four local ethics committees. The results of the study will be published in peer-reviewed journals and will be disseminated through national and international conferences. Trial registration number: ChiCTR1900021053